Study of the state of burnout in a group of caregivers: case of the provincial hospital El Idrissi, Kenitra, Morocco. - Khalid, CHAKHTOURA; Yassine, CHAIB; Anas, ELANSSARI; Youssef, ABOUSSALEH; Mahjoub, AOUANE; Samir, HAMMAMA; O.T.AHAMI, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The Burnout is a syndrome that can affect all social categories including nurses. This occupation requires an overload of activities throughout its exercise. The purpose of this work is to identify the risk factors that generate the burnout profile for this category of caregiver. We opted for a methodological kit already validated by our unit in the Moroccan context. The study was conducted at the Idrissi Provincial Hospital out of 96 caregivers of which 57.3% (n = 55) are female and 42.7% (n = 41) are male. The results show that 46.87% of nurses show signs of burnout. Indeed, 71.9% (n = 69) and 55.2% (n = 53) respectively had a high level of emotional exhaustion and depersonalization and 77.9% (n = 74) had a low level of degree of achievement. In addition, the multiple correspondence analysis shows that gender, seniority and age are factors contributing to burnout. To conclude these preliminary results constitute an emergency call for the leaders in order to put in place the necessary conditions to fight this plague with serious consequences on the general health status of caregivers.